Determination the changes in water and vegetation covers for Ain Al Tomar district using remote sensing techniques - Ahmed Efan Rusul; Albakry Sundus A. Abdullah (E3S Web of Conferences)
Ain Al Tamor district is one of administration units of Karbala province m middle Iraq. The aim of the study is analyze the changes in vegetation area using the Normalized Difference Vegetation Index (NDVI) and the Normalized Difference Water Index (NDWI) for 1990. 2000, 2013 and 2024. Landsat 5 TM and Landsat 8 OLI used to extract the vegetation and water covers for study period. The results of the study showed that there is a clearly increase in the NDVI for Ain Al Tamor m 1990, 2000. 2013. 2024 ranged from 45.2 km2, 67.2 km2, 146.3 km2 and 266.3 km2, respectively. The study area depends on ground water for irrigation of the crops, especially the palm orchards. On the other hands. NDWI values recorded decrease values for the same years about 515.5 km2 in 1990, 414.3 km2 in 2000. 161.5 km2 in 2013 and 183.1 km2 in 2024. These fluctuations of water area due to decline of precipitation values in the study area and shrink of surface water. The study of vegetation and water covers is important, especially in desert and semi desert regions for stability of local populations, rural development, sustainable development and increasing agricultural cover.